Numerical investigation of heat transfer of a multi-layered microchannel heat sink with tapered channel - Zuo, Jiawei (2023)
With the ever-growing development of microelectronic equipment, a more efficient heat dissipation method is in demand. The present study seeks to enhance the heat transfer characteristic in microchannel heat sink (MCHS), while maintain low power consumption by using multi-layered microchannels, different flow configurations and tapered channel profile.